Glass material and their advanced applications - Rajaramakrishna, R; Kaewkhao, Jakrapong (KnE Social Sciences, 2019)
The present review summarizes the progress made in the area of glass science and also propose new definition of glass. The applications of glasses in everyday life and especially glasses used for light emitting devices, optical displays, optical fibers, amplifiers, lasers which are of special interest. Among these materials rare earth ions doped glasses are of great important to optoelectronics and are widely used in optical fiber amplifiers and solid state high power lasers for telecommunications and light emitting diodes. Optical fiber revolutionized the glass industry and is been used as sensing applications which depends upon light wavelength, fiber parameters, fiber geometry, and metal layer properties. Even smart glasses play a vital role in the medical field.